Secercah Hati - V. Santi Paramita; Iis Isnayati; Yusep Ikrawan; Tania Adialita (MITRA: Jurnal Pemberdayaan Masyarakat, 2019)
The poverty level of urban communities, indicated by the high rate of maternal and infant mortality, the presence of stunting problems, and the poor health of the elderly in the Cibereum Village, Cimahi City, have an impact on the lack of concern for individual health and environmental health. The Secercah Hati program is created with the purpose of overcoming such problems. This program is a community empowerment program to create a healthy, knowledgeable, and prosperous society by increasing the role of women. It is collaborating with the Cimahi City Government Program, based on the 2017-2022 Cimahi City Medium Term Development Plan (RPJMD). Furthermore, the Secercah Hati Program is also an implementation of a partnership which is not only between Jenderal Achmad Yani University and the Cimahi City Government but also with Pasundan University. The program attempts to solve the issues by improving the role of Posyandu and Posbindu. The method of activity begins with a situation analysis that is coordinated with Cimahi City Government, problem identification, gathering and analyzing needs, determining priority problems, providing solutions, implementing, and evaluating. This participatory empowerment activity was carried out by forming a women's community consisting of Posyandu and Posbindu managers. Empowerment was implemented through training, workshops, mentoring, and role play (theatrical), so that they could optimize their role in improving public health and the environment and supporting the family economy. They were taught the ability to produce culinary with strong branding and market products utilizing digital marketing. In addition, they learnt to manage capital to support business sustainability. The program has an impact on increasing the number of cadres and the level of community participation in Posyandu and Posbindu activities, increasing the number of women entrepreneurs and increasing community income. The success of this community empowerment program needs to be supported by the concept of exciting and measurable activities in order to get a positive response from the community. Mentoring activities would be conducted continuously until the community is accustomed to and able to run programs independently and this is one of the keys to success. Implementing activities that synergize the Regional Government, Universities, and the community have proven to make the community empowerment program more effective.